2011
DOI: 10.1007/s12088-011-0210-6
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Spectrum and Antimicrobial Susceptibility Pattern of Bloodstream Infections in Children with Febrile Neutropenia: Experience of Single Center in Southeast of Turkey

Abstract: Empirical antimicrobial therapy is usually started in febrile neutropenic patients without having culture results. The aim of this study was to help determine the policies of empirical antibiotic usage in febrile neutropenic children by detecting the antimicrobial susceptibility profile in this group of patients. In this study 811 blood cultures taken from neutropenic children hospitalized at the Department of Oncology of Gaziantep Children Hospital November 2007 and February 2010 were retrospectively evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 30 publications
5
16
0
Order By: Relevance
“…Secondly, in 13 of the studies the bacterial isolates were collected during episodes of febrile neutropenia [7,8,10,11,13,14 & ,17,18,20,21,26,29]. Thirdly, the bacteria were isolated from different sources; 16 studies included BSIs only [7,8,[10][11][12]14 & , 15-18, 21,22,24,25 & ,27,29], and eight studies isolated the bacteria from clinical (and/or surveillance) samples for which the percentage of bloodstream isolates ranged from 42.9 to 74.8% in five studies [6,19,23,26,28] and was not reported in the remaining three [9,13,20]. Thirdly, the bacteria were isolated from different sources; 16 studies included BSIs only [7,8,[10][11][12]14 & , 15-18, 21,22,24,25 & ,27,29], and eight studies isolated the bacteria from clinical (and/or surveillance) samples for which the percentage of bloodstream isolates ranged from 42.9 to 74.8% in five studies [6,19,23,26,28] and was not reported in the remaining three [9,13,20].…”
Section: Current Trends In the Epidemiology Of Bacterial Infections Imentioning
confidence: 99%
See 3 more Smart Citations
“…Secondly, in 13 of the studies the bacterial isolates were collected during episodes of febrile neutropenia [7,8,10,11,13,14 & ,17,18,20,21,26,29]. Thirdly, the bacteria were isolated from different sources; 16 studies included BSIs only [7,8,[10][11][12]14 & , 15-18, 21,22,24,25 & ,27,29], and eight studies isolated the bacteria from clinical (and/or surveillance) samples for which the percentage of bloodstream isolates ranged from 42.9 to 74.8% in five studies [6,19,23,26,28] and was not reported in the remaining three [9,13,20]. Thirdly, the bacteria were isolated from different sources; 16 studies included BSIs only [7,8,[10][11][12]14 & , 15-18, 21,22,24,25 & ,27,29], and eight studies isolated the bacteria from clinical (and/or surveillance) samples for which the percentage of bloodstream isolates ranged from 42.9 to 74.8% in five studies [6,19,23,26,28] and was not reported in the remaining three [9,13,20].…”
Section: Current Trends In the Epidemiology Of Bacterial Infections Imentioning
confidence: 99%
“…Out of the remaining 11 studies, in five the rates of patients with neutropenia ranged from 39.4 to 62.2% [16,23,24,27,28]; in the other six studies, while neutropenic patients accounted for a large proportion of the patient population, the exact rate was not reported [6,9,15,19,22,25 & ]. Finally, the reported studies were conducted in different geographic areas: 11 studies in Asia [8,10,11,13,[15][16][17]19,22,26,29], nine in Western Europe [9,14 & ,18,20,21,24,25 & ,27,28], and four in the Middle East [6,7,12,23]. Finally, the reported studies were conducted in different geographic areas: 11 studies in Asia [8,10,11,13,[15][16][17]19,22,26,29], nine in Western Europe [9,14 & ,18,20,21,24,25 & ,27,28], and four in the Middle East [6,7,12,23].…”
Section: Current Trends In the Epidemiology Of Bacterial Infections Imentioning
confidence: 99%
See 2 more Smart Citations
“…More importantly, community-acquired infections due to MRSA have become increasingly problematic in recent years [1,2]. Linezolid is an oxazolidinone antibiotic with good activity against drug resistant Gram-positive bacteria such as MRSA [3][4][5]. The mechanism of action of linezolid involves the inhibition of bacterial protein synthesis through binding to the domain V regions of the 23 S rRNA gene [6].…”
Section: Introductionmentioning
confidence: 99%